Does Transient Receptor Potential Vanilloid Type 1 Alleviate or Aggravate Pathological Myocardial Hypertrophy? - Yan, Qiqi; Tang, Jun; Zhang, Xin; Wu, Liuyang; Xu, Yunyi; Wang, Lihong (Frontiers in Pharmacology, 2021)
Transient receptor potential vanilloid type 1 (TRPV1) is a non-selective cation channel, which is involved in the endogenous stress adaptation mechanism for protection of the heart as well as the occurrence and development of some heart diseases. Although the effect of activation of the TRPV1 channel on different types of non-neural cells in the heart remains unclear, most data show that stimulation of sensory nerves expressing TRPV1 or stimulation/overexpression of the TRPV1 channel has a beneficial role in heart disease. Some studies have proven that TRPV1 has an important relationship with pathological myocardial hypertrophy, but the specific mechanism and effect are not clear. In order to help researchers better understand the relationship between TRPV1 and pathological myocardial hypertrophy, this paper aims to summarise the effect of TRPV1 and the related mechanism in the occurrence and development of pathological myocardial hypertrophy from the following three points of view: 1) Role of TRPV1 in alleviation of pathological myocardial hypertrophy; 2) role of TRPV1 in aggravation of pathological myocardial hypertrophy; and 3) the point of view of our team of researchers. It is expected that new therapies can provide potential targets for pathological myocardial hypertrophy.